Pencabulan Anak Dalam Perspektif Hukum Pidana - Febrigi Rohalyati (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Obscenity is a violation of children's rights and there is no argument that can justify this crime, both from a moral, ethical and religious point of view, especially the criminal act of obscenity committed against the accused and minors. The purpose of this research is to find out the criminal law perspective on child abuse. The research method used is normative legal research. Criminal law has an important role in protecting children, providing sanctions for perpetrators, and providing protection and rehabilitation for victims. The legal system must provide effective protection mechanisms, including the provision of legal aid, identity secrets, and escorting victims during the legal process.